Knowledge and Practice of Mother regarding Exclusive Breastfeeding having Infant at a Tertiary Level Hospital, Kathmandu - Adhikari, TM (Journal of Nepal Paediatric Society, 2015)
Introduction: Promotion of exclusive breastfeeding is a cost effective intervention to reduce infant mortality in developing countries. The objective of this study was to identify knowledge and practice of mothers regarding exclusive breastfeeding. Material and Methods: This was a descriptive exploratory study carried out in the immunization clinic of tertiary level hospital in Kathmandu. A total of 323 mothers who came for immunization of six months to one year were selected as the sample for the study by using non-probability purposive sampling technique. Semi - structured interview questionnaire was used to collect the data both on knowledge and practice of exclusive breastfeeding, from 13th July to 8th September 2014. Results: Study findings revealed that 84.5 % of the respondents were aware of the correct meaning of exclusive breastfeeding and 49.5 % of the respondents practiced exclusively breastfeeding to their children up to 6 months. There was statistically significant association of respondent’s level of knowledge regarding exclusive breast feeding with their educational status (p = 0.034, OR = 1.7, 95% CI = 1.03-2.66) and type of delivery (p = 0.005, OR = 1.9, 95% CI = 1.2-3). Likewise, a significant association was seen between respondent’s level of practice regarding EBF and type of delivery (p = 0.005, OR = 1.9, 95% CI = 1.2-3). Conclusion: Study concludes that only about half of the mothers tended to have adequate knowledge regarding exclusive breast feeding. However, practice of exclusive breastfeeding for up to six months tended to be low so there should be efforts on encouraging and counseling for exclusive breast-feeding up to six months in hospital, community and immunization clinic.